In Vitro Assessment of Immunomodulatory Effects on HT-29 Cells and Antimicrobial Activity Against Enteropathogenic Bacteria of Lactobacillus plantarum LAB02 Newly Isolated from Guts of the Termite Termes sp. - Chanworawit, Kittipong; Deevong, Pinsurang (Trends in Sciences, 2025)
Probiotics are beneficial non-pathogenic microorganisms that inhabit gastrointestinal tracts and provide effective abilities such as preventing pathogenic infection, improving immune system and anti-inflammation enhancing the health of humans and animals. The objectives of this study were to evaluate antimicrobial capability against enteropathogenic bacteria and immunomodulatory effects of lactic acid bacteria isolated from termites. In the study, 5 isolates of lactic acid bacteria were obtained from the guts of the termite Termes sp. They were tested for the ability to inhibit growth potential of enteropathogenic bacteria using the agar well diffusion method and also their adhesion ability and cytotoxicity to human intestinal HT-29 cells. Among all 5 isolates, LAB02 exhibited strong broad-spectrum antimicrobial activity against all nine enteropathogenic bacteria, moreover it possessed non-toxicity and overall higher adhesion ability to HT-29 than the commercial probiotic Lactobacillus rhamnosus GG. Due to its high potential, LAB02 was selected for subsequent experiments. Based on nucleotide sequence analysis of 16S rRNA gene, LAB02 was closely related to Lactobacillus plantarum (100% identity). After inflammatory induction by lipopolysaccharide from Escherichia coli, immunomodulatory effects of LAB02 on the pathogen-induced HT-29 were evaluated in this study. The quantitative polymerase chain reaction (qPCR) assay was provided to measure gene expression level of pro- (IL-1, IL-6, IL-8, TNF-α and NF-κß) and anti-inflammatory cytokines (IL-4, IL-10, TGF-ß1, TGF-ß2 and TGF-ß3) and overall results revealed that LAB02 and its cell free supernatant could down-regulate the gene expression of pro-inflammatory cytokines and up-regulate of anti-inflammatory cytokines in HT-29 cells. The present study demonstrated some evidence indicating the potential of lactic acid bacteria obtained from termite guts. The strain Lactobacillus plantarum LAB02 might be used as a promising alternative agent to control enteropathogenic bacterial infection and modulate the immune system. The findings are useful for future study and applications in food microbiology and technology. HIGHLIGHTS The intestinal tract of termite Termes is a potential source of high-performance lactic acid bacteria. Agar well diffusion demonstrated strong broad-spectrum anti-enteropathogenic activity of the isolate Lactobacillus plantarum In addition to its non-toxicity and good adhesion ability to human intestinal HT-29 cells, quantitative polymerase chain reaction (qPCR) assay revealed a positive impact of the strain LAB02 on pro- and anti-inflammatory cytokine gene expression. The lactic acid bacteria Lactobacillus plantarum LAB02 has antimicrobial and immunomodulatory activity, promising as an effective alternative agent to control enteropathogenic bacterial infection and modulate the human immune system. GRAPHICAL ABSTRACT